Reconfiguration of the Lost Unity: The Convent of San Biagio in Vicenza, Italy - Pietrogrande, Enrico; Dalla Caneva, Alessandro (ICONARCH International Congress of Architecture and Planning, 2017)
This work concerns Vicenza, a city located not far from Venice in the north-east corner of Italy, and it specifically refers to the abandoned convent of San Biagio on the banks of the Bacchiglione river. Once intimately part of the city’s historic center, the area gradually lost its functional and social identity. The idea of restoring that degraded area of the city of Vicenza has long been the object of discussion on the part of local authorities. The convent of San Biagio is one of the subjects recently investigated by our students at the ‘Architectural and Urban Composition 2' course taught on the master’s degree in Architectural Engineering at the Department of Civil, Environmental and Architectural Engineering of the University of Padua. The working method is based on the belief that, in the study of urban morphology, is basic to analyse the history of the city, clarifying the relationship between permanent structures on the one hand and temporary ones on the other. The history becomes an indispensable tool to know the deep reasons of the urban structure which is the memory and the image of the community. The methodology looks at the city as a product of functional systems (political, social, economic), but overall contemplates the urban form as a result of its spatial structure. The life of the urban form is then investigated especially in its physical specificity, the only one able of giving reason of its special nature. The San Biagio area has been affected by heavy transformations that has resulted in the organic unity with surrounding parts of the city being lost. The order and hierarchy of the elements that characterize the form of this old place were compromised. The convent and the church of San Biagio in Vicenza were thought by our students as an opportunity to reconfigure the lost unity of a symbolic and representative place of the city, custodian of its memory and identity.